Factors associated with willingness and preferences to attend family services in Hong Kong: A population-based survey - Zeng, Yingpei; Gong, Weijie; Lai, Agnes Yuen Kwan; Sit, Shirley Man Man; Wang, Man Ping; Ho, Sai Yin; Lam, Tai Hing (Frontiers in Public Health, 2023)
Objective Family services are open to the community at large as well as vulnerable groups; however, little is known about the willingness of communities to attend such services. We investigated the willingness and preferences to attend family services and their associated factors (including sociodemographic characteristics, family wellbeing, and family communication quality) in Hong Kong. Methods A population-based survey was conducted on residents aged over 18 years from February to March 2021. Data included sociodemographic characteristics (sex, age, education, housing type, monthly household income, and the number of cohabitants), willingness to attend family services to promote family relationships (yes/no), family service preferences (healthy living, emotion management, family communication promotion, stress management, parent-child activities, family relationship fostering, family life education, and social network building; each yes/no), family wellbeing, and family communication quality (both scores 0–10). Family wellbeing was assessed using the average scores of perceived family harmony, happiness and health (each score 0–10). Higher scores indicate better family wellbeing or family communication quality. Prevalence estimates were weighted by sex, age and educational level of the general population. Adjusted prevalence ratios (aPR) for the willingness and preferences to attend family services were calculated in relation to sociodemographic characteristics, family wellbeing, and family communication quality. Results Overall, 22.1% (1,355/6,134) and 51.6% (996/1,930) of respondents were willing to attend family services to promote relationships or when facing problems, respectively. Older age (aPR = 1.37–2.30, P < 0.001–0.034) and having four or more cohabitants (aPR = 1.44–1.53, P = 0.002–0.003) were associated with increased aPR of willingness for both situations. Lower family wellbeing and communication quality were associated with lower aPR for such willingness (aPR = 0.43–0.86, P = 0.018–<0.001). Lower family wellbeing and communication quality were associated with preferences for emotion and stress management, family communication promotion, and social network building (aPR = 1.23–1.63, P = 0.017–<0.001). Conclusions Lower levels of family wellbeing and communication quality were associated with unwillingness to attend family services and preferences for emotion and stress management, family communication promotion, and social network building.